2013
DOI: 10.5539/jas.v5n10p20
|View full text |Cite
|
Sign up to set email alerts
|

Screening Ornamentals for Their Potential as As Accumulator Plants

Abstract: Arsenic-based pesticides, herbicides and insecticides are used in horticultural operations resulting in soil contamination around greenhouse structures. Phytoremediation and phytostabilization are two techniques for treating arsenic (As) contaminated soil. Several ornamental plant species, Iris (Iris savannarum), switchgrass (Panicum virgatum), Tithonia rotundiflora, Coreopsis lanceolata, sunflower (Helianthus annuus), and marigold (Tagetes erecta), were evaluated for their potential use as accumulator plants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Results for plant growth and As uptake were reported in Reed, Ayala-Silva, Dunn, Gordon, and Meerow (2013). In summary, based on dry weight, tithonia and coreopsis did not produce enough biomass to merit consideration for bioremediation.…”
Section: General Commentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Results for plant growth and As uptake were reported in Reed, Ayala-Silva, Dunn, Gordon, and Meerow (2013). In summary, based on dry weight, tithonia and coreopsis did not produce enough biomass to merit consideration for bioremediation.…”
Section: General Commentsmentioning
confidence: 98%
“…Additional harvests could substantially increase the amount of As removed. The uptake ratio and translocation factor at 5.25 mg As L -1 solution for each species is as follows: coreopsis -73.0 and 0.07, tithonia -33.4 and 1.13, sunflower -16.6 and 0.88, iris 6.7 and 9.21, marigold -7.4 and 1.20, and switchgrass -1.5 and 0.16 (Reed, Ayala-Silva, Dunn, Gordon, & Meerow, 2013). …”
Section: Tissue Arsenic Concentrationmentioning
confidence: 99%
“…Calendula can be used for phytoremediation of soils with low level of Cr (up to 10 ppm).Whereas in rose a higher concentration of chromium was found in roots than in shoot of the plant. Reed et al [18] investigated arsenic phytoremediation with various ornamental crops and found that only small amount of arsenic was found in iris root and shoot. Tithonia and coreopsis were most sensitive to arsenic exposure but had higher uptake ratio even in low arsenic concentrations.…”
Section: Role Of Flowers and Ornamentals In Phytoremedia-tionmentioning
confidence: 99%
“…Tithonia and Coreop-sis showed respectively 85% and 65% reductions in dry weight at 0.75 mg L -1 As concentration. At the highest As rate, marigold and sunflower had uptake ratios of 7.4 and 16.6, respectively, and TF near one, allowing consideration of these species as interesting candidates for As phytoremediation (Reed et al 2013).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%